Experimental and numerical investigation on mechanical behaviors of woven fabric composites under off-axial loading - Wang, Liang (2020)
A mesoscale finite element model was developed to investigate the progressive damage behaviors of twill woven composites under off-axial tension and compression. The anisotropic damage model based on the Murakami-Ohno damage theory was adopted to characterize the composites failure process, and a combined elastoplastic damage model was developed for modeling the mechanical behavior of the matrix. Effective tow properties were obtained based on micromechanical characterization of the fiber bundles, and the failure mechanisms at the tow constituent scale were also investigated. Moreover, experimental tension and compression tests were carried out on the woven specimens to obtain their mechanical responses under various off-axial loading conditions. The fracture surfaces of the test specimens were characterized by optical microscopy and the corresponding failure mechanisms were identified. The numerical predictions showed good agreement with the experimental result.